Algunas pistas y reflexiones en torno del dibujo rítmico como dinamizador de la lectoescritura musical en población rural desde el modelo de escuela nueva (2015)
Reading and writing music is very important in developing different abilities in children. The following article is a reflection of how rhythmic drawing planted by a Colombian, Tita Maya, we are able to strengthen students important aspects in their comprehensiveness like the rhythms, the spacial location, the coordination which you are able to hear through movement, the scribbling and music that play a prominent role during the process of the activity being investigated. After the significant processes, you leave the experience lived in a rural population from the southwestern Antioquia where people work for the multi area and multi grade. One investigation that was realized based through means of observation and the accompaniment of how the students respond from grades like preschool, elementary and middle school. From each activity planted, a result was obtained